Estrategias didácticas mediadas por las tic para el aprendizaje de la asignatura de ciencias naturales de los estudiantes del segundo año de educación básica de la unidad educativa “Oswaldo Villamil Auz” cantón Quevedo, período lectivo 2021-2022 - Lozano Veliz, Raquel Jesusa (2022)
Didactic strategies in the teaching of natural sciences start from the development of new technologies introduced in the classroom and with them, from the integration of new content and ways of learning, teaching. This vision translates into another vision of construction of the content of science, with the aim of adapting the student's work in their daily life, which leads to the construction of significant learning. The present investigation was consolidated in the "Oswaldo Villamil Auz" Educational Unit, which is located in the city of Quevedo in the Viva Alfaro parish. The development of this research required as a sample the group of teachers who teach classes in the morning section, resulting in 17 servers, and 58 parents to whom the survey instrument was applied, relevant to the diagnosis of the problem. The objective of the research is to analyze the didactic strategies mediated by the use of ICT as support for the teaching-learning process in the subject of Natural Sciences of the second-year students of Basic Education of the Educational Unit Oswaldo Villamil Auz, of the canton Quevedo during the 2021-2022 school period. The method used for the research was inductive-deductive, because it allows identifying the existing problem, it is also a qualitative and quantitative study and the results of the research show the importance of the use of didactic strategies mediated by ICT in the educational field